Estudo de nanoestruturas de titanato como catalisadores heterogêneos aplicados na síntese de carbonato de glicerol - Scheid, Carolina Majolo (2019)
Glycerol, which comes from 10% of biodiesel production, has been attracting attention in recent times due to its wide applicability in the industry, as for the synthesis of glycerol carbonate (GC). Among the different forms of GC synthesis, an alternative is the glycerol transesterification reaction with dimethyl carbonate (indirect route). However, it is necessary to use catalysts to reach high conversions and selectivity of glycerol carbonate, such as sodium titanate nanotubes (NaTNT) which are shown to be efficient for different reactions (production of biodiesel, another carbonates, among others). Within the context of sustainability, these nanostructures present low cost of production, as well as the opportunity to perform reuse. Thus, the uncalcined and calcined NaTNTs at 300, 500, 600 and 700 ° C were developed in this work in order to produce glycerol carbonate (indirect route). The morphological and structural evaluation of the catalysts revealed the change of nanotubes to nanorods and the transition from anatase to ruthenic phase, when the catalyst was calcined at 700 ° C (NaTNT700). The NaTNT, NaTNT500 and NaTNT700 catalysts show specific surface area values of 155, 88, 19 m².g-1, respectively, as well as a decrease in pore diameter as the calcination temperature increased and it was not possible to determine for or NaTNT700. The results of catalytic carbonation reaction by indirect route showed high conversions of glycerol (≈ 99%) and selectivities in GC (≈ 100%). In addition, the high purity GC was synthesized as shown by ¹H-NMR analysis.